Sarcopenia: prevalence, associated factors, and the risk of mortality and disability in Japanese older adults. Issue 1 (25th November 2020) - Kitamura, Akihiko; Seino, Satoshi; Abe, Takumi; Nofuji, Yu; Yokoyama, Yuri; Amano, Hidenori; Nishi, Mariko; Taniguchi, Yu; Narita, Miki; Fujiwara, Yoshinori; Shinkai, Shoji
Abstract: Background: There is limited evidence on sarcopenia in Asian populations. This study aimed to clarify the prevalence, associated factors, and the magnitude of association with mortality and incident disability for sarcopenia and combinations of its components among Japanese community‐dwelling older adults. Methods: We conducted a 5.8 year prospective study of 1851 Japanese residents aged 65 years or older (50.5% women; mean age 72.0 ± 5.9) who participated in health check‐ups. Sarcopenia was defined according to the Asian Working Group for Sarcopenia 2019 algorithm. Appendicular lean mass index (ALMI) was measured using direct segmental multi‐frequency bioelectrical impedance analysis. A Cox proportional hazards regression model was used to identify associations of sarcopenia and the combinations of its components with all‐cause mortality and incident disability. Results: The prevalence of sarcopenia was 11.5% (105/917) in men and 16.7% (156/934) in women. Significant sarcopenia‐related factors other than ageing were hypoalbuminaemia, cognitive impairment, low activity, and recent hospitalization (all P ‐values <0.05) among men and cognitive impairment ( P  = 0.004) and depressed mood ( P  < 0.001) among women. Individuals with sarcopenia had higher risks of mortality [hazard ratios (95% confidence interval): 2.0 (1.2–3.5) in men and 2.3 (1.1–4.9) in women] and incident disability [1.6 (1.0–2.7) in men and 1.7 (1.1–2.7) in women]. Compared with the individuals without any sarcopenia components, those having low grip strength and/or slow gait speed without low ALMI tended to have an increased risk of disability [1.4 (1.0–2.0), P  = 0.087], but not mortality [1.3 (0.8–2.2)]. We did not find increased risks of these outcomes in participants having low ALMI in the absence of low grip strength and slow gait speed [1.2 (0.8–1.9) for mortality and 0.9 (0.6–1.3) for incident disability]. Conclusions: Japanese older men and women meeting Asian criteria of sarcopenia had increased risks of all‐cause mortality and disability. There were no significant increased risks of death or incident disability for both participants with muscle weakness and/or low performance without low muscle mass and those with low muscle mass with neither muscle weakness nor low performance. Further studies are needed to examine the interaction between muscle loss, muscle weakness, and low performance for adverse health‐related outcomes.